Assessing the role of radiotherapy in patients with refractory or relapsed high-grade B-cell lymphomas treated with CAR T-cell therapy. (October 2022) - Ababneh, Hazim S.; Abramson, Jeremy S.; Johnson, P. Connor; Patel, Chirayu G.
Highlights: CD19-targeted CAR T-cell therapy has led to remarkable survival improvements. Bridging therapy is required to control the disease during the manufacturing process. Radiation therapy is a promising bridging approach with favorable outcomes in chemorefractory disease. Radiation therapy could also be considered as a salvage approach following CAR T-cell therapy failure. Abstract: An estimated 30–40% of patients with diffuse large B cell lymphoma (DLBCL) will either relapse or have refractory disease with first-line chemoimmunotherapy. The standard approach for relapsed/refractory disease is salvage chemotherapy followed by autologous stem cell transplantation, but this approach cures fewer than 20% of patients in the modern era. This low cure rate is a result of refractory disease despite salvage therapy, medical ineligibility for transplantation, or relapse following transplantation. CD19-targeted chimeric antigen receptor (CAR) T-cell therapy has revolutionized the treatment paradigm for patients with relapsed or refractory disease, leading to response rates that range between 52% to 93%, and overall survival rates at one year between 48% and 83%. However, the time from apheresis to infusion of CAR T-cell therapy currently takes several weeks, leaving many patients in need of bridging therapy to control disease progression. Radiation therapy (RT) has been utilized as a bridging therapy prior to CAR T infusion in select patients, with some remarkable responses in chemorefractory disease. Furthermore, the potential synergy between RT and CAR T-cells due to immunomodulatory mechanisms has generated considerable excitement, as it has been hypothesized that RT could also be considered as a salvage therapy following CAR T failure, based on limited case series published to date. Prospective trials are warranted to validate the significance of this modality following CAR T-cell therapy.